A Review on Pathophysiology and Treatmnent Approaches of Huntington's Disease - tiwari, Akhilesh (International Journal of Pharmaceutical & Biological Archive, 2022)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-hansi-font-family:Calibri;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Huntington's disease is a complex degenerative disorder that affects the central nervous system. Huntington's disease is an autosomal-dominant, progressive neurodegenerative disorder typically presents during mid-life with a distinct phenotype, including chorea and dystonia, incoordination, cognitive decline, and behavioural difficulties. Attempts to study early disease are not unique in neurology (e.g., mild cognitive impairment and vascular cognitive impairment), but studying otherwise healthy-appearing individuals who have nearly 99% certainty of manifesting the symptoms of brain disease does provide distinct but valuable information about the true natural history of the disease. The review aims majorly on four areas namely: mehanisms, features, treatment and other aspects of Huntington’s disease.